ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PERUSAHAAN MELAKUKAN PERGANTIAN KAP - Anita Novianti; Muhamad Nuryatno (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2017)
The main purpose of this research is examining the effects of audit opinion, .linancial distress, ICAP size, firm size, and management changes to auditor switching. This research is using data of manufacture company in Indonesia in the period 2005— 2010. The researcher uses purposive sampling and get total sample are 234 research data. The data is examined with logistic regressin in SPSS 19 software. Result of this research show that KAP size has significant effect on auditor switching, while other factors like audit opinion, financial distress, firm size, and management changes do not have significant effect on auditor switching.